Towards ecologically sustainable world food production - Pinstrup-Andersen, Per (1999)
Improved production methods, and appropriate use of inputs and technology, can boast [i.e. boost] productivity in ways that are beneficial for the environment. Past successes in food production resulted in increases in per capita food availability, but they occurred in part at the expense of natural resources. Rapidly increasing yields reduced the expansion of agriculture into new lands and thus had positive effect on biodiversity, wildlife and soils. Negative impacts included the introduction of large quantities of chemical pesticides, as well as water and soil degradation. The key question for the future is not whether natural resources will be adequate to feed future generations, but whether the necessary policies and technologies will be introduced.